METHODS FOR DEVELOPING NEW MACHINE LEARNING ALGORITHMS - Alkhanova, Г.А.; Alimbekova, И.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
Modern challenges in the field of data analysis require a rethinking of machine learning methods and the development of new algorithms capable of adapting to unstable and often uncertain environments. This article examines methodological aspects of designing new machine learning algorithms, including the formalization of learning tasks, model construction, loss function selection, and regularization strategies. The need to shift from universal approaches to more context-aware architectures is substantiated, as such models can maintain a balance between accuracy, interpretability, and computational efficiency. Particular attention is given to factors limiting the applicability of existing solutions: overfitting, low noise robustness, high computational costs, and lack of decision transparency. A classification of common challenges faced during algorithm development is proposed, divided into three levels: theoretical (modeling and justification), technical (infrastructure and resources), and applied (data quality, legal and ethical constraints). The methodological basis of the study includes elements of systems analysis, literature review, and expert interpretation of empirical observations. The results allow for systematization of key principles in the design of machine learning algorithms and outline directions for adapting them to real-world scenarios. The findings emphasize the importance of an interdisciplinary approach that integrates mathematical methods, engineering solutions, and ethical responsibility in the deployment of intelligent systems.